2010
DOI: 10.1080/00268971003698056
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational predissociation spectra of the Ar-tagged [CH4· H3O+] binary complex: spectroscopic signature of hydrogen bonding to an alkane

Abstract: 2010) Vibrational predissociation spectra of the Ar-tagged [CH 4 · H 3 O + ] binary complex: spectroscopic signature of hydrogen bonding to an alkane, Vibrational predissociation spectra of the Ar-tagged [H 3 O þ Á X], X ¼ CH 4 , CD 4 , N 2 , and Ar complexes are analysed to explore the hydrogen bonding acceptor properties of an alkane. The observed red shift in the OH stretching transition of the donor is found to be significantly smaller than anticipated by the previously reported trend in this value with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 42 publications
(49 reference statements)
1
21
0
Order By: Relevance
“…The features in this region have been discussed at length in earlier work by us and by Duncan and co-workers. 2,21,53 Qualitatively, the systematic blue-shift of the a-band with increasing strength of the solvent interaction is consistent with the expected behavior of the bend-rotation combination band. Indeed, the calculated harmonic spectra of these complexes, as shown in the right columns of Table 1, follow the same trends as the spacing between the a-band and n HOH .…”
Section: Iiib Calculated Spectrasupporting
confidence: 80%
See 1 more Smart Citation
“…The features in this region have been discussed at length in earlier work by us and by Duncan and co-workers. 2,21,53 Qualitatively, the systematic blue-shift of the a-band with increasing strength of the solvent interaction is consistent with the expected behavior of the bend-rotation combination band. Indeed, the calculated harmonic spectra of these complexes, as shown in the right columns of Table 1, follow the same trends as the spacing between the a-band and n HOH .…”
Section: Iiib Calculated Spectrasupporting
confidence: 80%
“…Here, the evolution of the bands as the proton affinity of the ligands is varied is informative, as the HOH bending transition in the H 3 O + core ion (labeled n HOH ) is observed to systematically blue-shift through the series (green line), while at the same time the symmetric and asymmetric OH stretches (highlighted in blue), which account for the dominant band in the mid-IR at B3300 cm À1 in H 3 O + ÁAr 3 (Fig.4b) dramatically red-shift down to B2650 cm À1 in H 3 O + Á(H 2 O) 3 ÁAr (Fig.4e). The features in this region have been discussed at length in earlier work by us and by Duncan and co-workers 2,21,53.…”
mentioning
confidence: 62%
“…However, to the best of our knowledge, systematic studies of messenger-dependent isomer-selectivity have never been reported. Although IR spectroscopy has been reported for phenol + ÁM m , 58 H 2 O + ÁM m , [53][54][55]57 H 3 O + ÁM m , 9,10,65,66 21,22 (M = rare gas, H 2 , N 2 , CH 4 ), and so on, isomerization in the moieties of interest cannot be expected in these relatively rigid systems.…”
Section: Introductionmentioning
confidence: 99%
“…The noble gas-tagging technique 109,110 mentioned in the previous paragraph has recently been employed to investigate the IR absorptions of various non-metal cations. [136][137][138][139][140][141][142][143][144][145] It is first of interest to mention the "Eigen" (H 3 O + ) and the "Zundel" (H 2 O-H-OH 2 + ) cations, the two limiting forms of proton accommodation in water. The relative weight of these two ions essentially depends on the number of solvating water molecules and this stimulates considerable interest for the structure and stability of H + (H 2 O) n clusters of variable size.…”
mentioning
confidence: 99%
“…The experimental results are invariably supported by ab initio or DFT calculations and detailed accounts of exemplary results had already been reported in review articles. 109,146,149 At variance with the above-mentioned applications of the Ng-tagging technique, [136][137][138][139][140][141][142][143][144][145] more emphasis is placed in these studies on the ion-ligand interactions and bonding motifs. A good recent illustrative case is the complexes of Ar with protonated benzaldehyde (BZH + ).…”
mentioning
confidence: 99%